2022
DOI: 10.3390/insects13100875
|View full text |Cite
|
Sign up to set email alerts
|

Inheritance of Resistance to Cry1A.105 in Helicoverpa zea (Boddie) (Lepidoptera: Noctuidae)

Abstract: Cry1A.105 is a bioengineered Bacillus thuringiensis (Bt) insecticidal protein consisting of three domains derived from Cry1Ac, Cry1Ab, and Cry1F. It is one of the two pyramided Bt toxins expressed in the MON 89034 event, a commonly planted Bt maize trait in the Americas. Recent studies have documented that field resistance of the corn earworm, Helicoverpa zea (Boddie), to the Cry1A.105 toxin in maize plants has become widespread in the United States. To investigate the inheritance of resistance to Cry1A.105 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Studies using F2 screening methods have reported high levels of resistance alleles to individual Cry toxins in H. zea populations from southeastern states. Yu et al [36] showed RAFs averaging 0.41 for Cry1A.105 and 0.33 for Cry2Ab2, while Santiago-Gonzalez et al [53] estimated RAF to be 0.722 (95%CL: 0.688-0.764) for Cry1Ac and 0.217 (95%CL: 0.179-0.261) for Cry2Ab2. Altogether, given these studies, the high PFRs at most trial locations, and the reduced control efficacy in the field, the evidence clearly documents widespread H. zea resistance to Cry1A.105 and Cry2Ab2.…”
Section: Phenotypic Resistance and Estimated Range Of Resistance Alle...mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies using F2 screening methods have reported high levels of resistance alleles to individual Cry toxins in H. zea populations from southeastern states. Yu et al [36] showed RAFs averaging 0.41 for Cry1A.105 and 0.33 for Cry2Ab2, while Santiago-Gonzalez et al [53] estimated RAF to be 0.722 (95%CL: 0.688-0.764) for Cry1Ac and 0.217 (95%CL: 0.179-0.261) for Cry2Ab2. Altogether, given these studies, the high PFRs at most trial locations, and the reduced control efficacy in the field, the evidence clearly documents widespread H. zea resistance to Cry1A.105 and Cry2Ab2.…”
Section: Phenotypic Resistance and Estimated Range Of Resistance Alle...mentioning
confidence: 99%
“…Early resistance monitoring studies and reports by registrants did not show strong evidence of significant changes in the baseline level of susceptibility to Bt toxins in corn earworm/cotton bollworm (Helicoverpa zea (Boddie) Lepidoptera: Noctuidae) populations [25][26][27]. However, more recent studies demonstrate widespread field-evolved resistance in H. zea to Cry1Ab, Cry1Ac, Cry2Ab2, and Cry1A.105 in Bt corn and Bt cotton [28][29][30][31][32][33][34][35][36][37][38][39]. Helicoverpa zea is not highly susceptible to Cry toxins, implying that key conditions underlying the success of the refuge strategy (i.e., high dose, recessive inheritance, and complete redundancy killing) for Bt crops producing these toxins may not be met [40][41][42].…”
Section: Introductionmentioning
confidence: 99%